MMPI-2-RF Profiles in Child Custody Litigants - Mazza, Cristina; Burla, Franco; Verrocchio, Maria Cristina; Marchetti, Daniela; Di Domenico, Alberto; Ferracuti, Stefano; Roma, Paolo (Frontiers in Psychiatry, 2019)
A psychological assessment of parents in post-divorce child custody disputes highlighted parents’ motivation to appear as adaptive and responsible caregivers. The study hypothesized that personality self-report measures completed by child custody litigants (CCLs) during a parental skills assessment would show underreporting, rendering the measures worthless. The study also analyzed gender differences in a CCL sample, general CCL profiles, and the implicit structure of the MMPI-2-RF in the CCL sample. The sample comprised 400 CCLs undergoing personality evaluation as part of a parenting skills assessment. The mean age of the 204 mothers was 41.31 years (SD = 6.6), with an overall range of 24–59 years. Mothers had a mean educational level of 14.48 years (SD = 3.2). The 196 fathers were aged 20–59 years (M = 42.31; SD = 7.8), with an average of 14.48 years (SD = 3.9) of education. The MMPI-2-RF was administered. To test the hypotheses, MANOVAs and two-step cluster analyses were run. CCL subjects reported higher scores in underreporting (L-r and K-r) and lower scores in overreporting (F-r, Fp-r, Fs-r, and RBS) validity scales and RC scales, with the exception of RC2 and RC8. RC6 (Suspiciousness) was the most elevated. Intercorrelations within the RC scales significantly differed between CCL and normative samples. Women appeared deeply motivated to display a faking-good defensive profile, together with lower levels of cynicism and antisocial behaviors, compared to CCL men. Two-step cluster analyses identified three female CCL profiles and two male CCL profiles. Approximately 44% of the MMPI-2-RF profiles were deemed possibly underreporting and, for this reason, considered worthless. The present study adds useful insight about which instruments are effective for assessing the personality characteristics of parents undergoing a parental skills assessment in the context of a child custody dispute. The results show that almost half of the MMPI-2-RF protocols in the CCL sample were worthless due to their demonstration of an underreporting attitude. This highlights the necessity to interpret CCL profiles in light of normative data collected specifically in a forensic setting and the need for new and promising methods of mainstreaming and administering the MMPI-2-RF.